Analysis of Atmospheric Conditions during the Occurrence of Mesoscale Convective Complex (MCC) in East Kalimantan and Surrounding Area (Case Study: December 26, 2021) - Daffa Adhitiansyah; Yosafat Donni Haryanto (Universitas Negeri Semarang, 2023)
Mesoscale Convective Complex (MCC) was first introduced in 1980 through research on infrared (IR) satellite images by Maddox. The MCC phenomenon can caused rain with a long period of time. This study aims to determine the atmospheric conditions when MCC occurred in East Kalimantan and surroundings area on December 26, 2021. The research data used in this study is Himawari-8 satellite data to display cloud top temperatures and convective cloud distribution using the CCO method and image interpretation using RGB method. Analysis of atmospheric conditions was also carried out on air humidity, vertical velocity, and reflectivity in the atmosphere obtained from weather radar data from the Stasiun Meteorologi Sultan Aji Muhammad Sulaiman - Sepinggan. Based on the results of the analysis, MCC was identified as a mature phase on December 26, 2021 at 12.00 UTC. Airmass RGB analysis shows the presence of clouds which are known as Cb clouds through CCO analysis as well as warm air masses with high humidity in East Kalimantan. Negative value of vertical velocity also indicates an updraft of moist air masses and the maximum reflectivity value of the CMAX product, which is 53 dBz, indicates strong convection activity.